Method for improving photoluminescence efficiency and stability of blue-light cesium-lead-bromine perovskite quantum dots
By synthesizing and liganding the CsPbBr3 quantum dots in a precursor solution rich in halogen lead, the problem of insufficient luminescence efficiency and stability of blue light perovskite quantum dots is solved, and high efficiency and long-term stable blue light luminescence effect is achieved. It provides a foundation for the preparation of blue light perovskite optoelectronic devices.
Patent Information
- Application Number
- CN202411281158.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-02-21
AI Technical Summary
Blue light perovskite quantum dots have shortcomings in terms of luminescence efficiency and stability, especially small-sized CsPbBr3 quantum dots lead to a large number of surface defects due to their huge specific surface area, resulting in low photoluminescence efficiency and are easily lost during purification or processing. Colloid stability and structural integrity.
The precursor solution of halogen-rich lead was added to the precursor solution of oleic acid and cesium carbonate to obtain a crude solution of CsPbBr3. After purification and synthesis of the ligand solution, didodecyldimethylammonium bromide and bromide were added by addition of didodecyldimethylammonium bromide and bromide Lead performs ligand exchange, modify the surface of quantum dots, and improves photoluminescence efficiency and stability.
Through this method, the photoluminescence efficiency of CsPbBr3 quantum dots is close to 100%, and has excellent stability under continuous ultraviolet radiation and environmental conditions, meeting the preparation needs of blue light perovskite optoelectronic devices.
Smart Images

Figure CN119490848A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of luminescent materials, and in particular to a method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots. Background Art
[0002] All-inorganic cesium lead halide perovskite materials have attracted widespread attention from scientific researchers in many fields such as light-emitting diodes, backlight displays, lasers, photovoltaics and photodetectors due to their high photoluminescence quantum yield (PLQY), narrow emission full width at half maximum (FWHM), easily adjustable band gap, high light absorption coefficient and defect tolerance.
[0003] Blue light perovskite quantum dots lag far behind red and green light perovskite quantum dots in terms of luminescence efficiency and stability due to their wider band gap, deep energy level traps and other problems. As the basis for full-color display and solid-state lighting applications, how to prepare efficient and stable blue light perovskite quantum dots is a key goal of current research. Generally, blue light emitting perovskites can be obtained by applying component engineering and quantum confinement effects. Compared with mixed halide perovskites, the quantum confinement effect of perovskite quantum dots provides an additional method to adjust the emission wavelength and avoid the generation of chlorine vacancies and the segregation of halides. However, for small-sized CsPbBr3 quantum dots, their huge specific surface area promotes the generation of a large number of surface defects, resulting in low PLQY. In addition, due to the characteristics of ionic bonding of perovskite quantum dots, they are prone to lose colloidal stability and structural integrity during purification or processing. Therefore, perovskite quantum dots require suitable surface passivation to obtain efficient and stable emitters.
[0004] Surface ligands play an important role in the synthesis, surface passivation, colloidal stability and regulation of optoelectronic properties of perovskite quantum dots. In recent years, surface ligand engineering of blue perovskite quantum dots has been widely studied and some progress has been made, such as the literature (Chen, YF; Nan, M.; He, YX; Lu, S.; Shen, W.; Cheng, G.; Chen, SF; Huang, W. Z-Type Ligand Enables Efficient and Stable Deep-Blue Perovskite Light-Emitting Diodes. ACSAppl. Mater. Interfaces 2024, 16 (17), 22139-22146.) reported CsPbBr3 perovskite quantum dot light-emitting diodes (λem : 464 nm), with a peak external quantum efficiency of 5.46%. However, its PLQY is lower than 75%, and there is still a problem of low photoluminescence efficiency of quantum dots, which is difficult to meet the application index requirements. In addition, the scheme lacks systematic research on the stability of perovskite quantum dots under different application environment conditions, which also restricts the applicability of blue light perovskite quantum dots.
[0005] Based on this, it is of great practical significance to combine surface ligand engineering to prepare high-efficiency blue light CsPbBr3 perovskite quantum dots that are long-term stable under various environmental conditions (such as ultraviolet light, heat, moisture, etc.). Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, a method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots is provided, comprising the following steps: (1) adding oleic acid and cesium carbonate to a halogen-rich lead precursor solution to react and obtain a CsPbBr3 crude solution; purifying, dissolving, and recovering the reaction product in the CsPbBr3 crude solution to obtain CsPbBr3 quantum dots; wherein the halogen-rich lead precursor solution is prepared by dissolving lead bromide, zinc bromide, and a ligand reagent in an organic solvent; (2) Adding a ligand solution to the CsPbBr3 quantum dots for post-synthesis treatment to improve the photoluminescence efficiency and stability; wherein the ligand solution is prepared by dissolving didodecyl dimethyl ammonium bromide and lead bromide in an organic solvent; after the ligand exchange of the post-synthesis treatment is completed, purifying, dissolving, and recovering the product to obtain surface-modified blue-light cesium lead bromide perovskite quantum dots.
[0007] Preferably, in step (1), the molar ratio of lead bromide to zinc bromide in the halogen-rich lead precursor solution is 1:(4-5).
[0008] Further preferably, the ligand reagent is a mixture of oleic acid and oleylamine in a volume ratio of 1:1; the molar ratio of lead bromide to oleic acid in the ligand reagent is 1:(23-28).
[0009] Those skilled in the art can determine the appropriate type and amount of organic solvent according to the solubility of the raw materials. As presented in one or more embodiments of the present invention, 1-octadecene and other dissolving raw materials can be used to create a suitable reaction environment. This method describes the core process of the reaction of a halogen-rich lead precursor solution with oleic acid and cesium carbonate to form CsPbBr3 quantum dots; in actual operation, in order to ensure the smooth progress of the reaction, cesium carbonate can be pre-heated with oleic acid in a solution environment created by the solvent to form a cesium precursor solution in advance; similarly, in the preparation process of the halogen-rich lead precursor solution, lead bromide, ligand reagents and organic solvents are mixed respectively, zinc bromide, ligand reagents and organic solvents are mixed, and lead bromide and zinc bromide are dissolved to form solutions and then blended to form a halogen-rich lead precursor solution. The above steps can be used as a guide to reduce the complexity of the actual operation. It does not change the substantial reaction of the halogen-rich lead precursor solution with oleic acid and cesium carbonate to form CsPbBr3 quantum dots. Those skilled in the art can also use other suitable operations to realize the process of the reaction.
[0010] Preferably, in step (1), the molar ratio of cesium carbonate to oleic acid is 1:(8-11).
[0011] By controlling the size of colloidal nanoparticles in a halogen-rich synthesis environment and at a relatively low synthesis temperature, the synthesized quantum dots can have a relatively small size and a uniform particle size distribution. The temperature and time of the reaction of the present invention are suitably controlled within a selected range, so that the synthesized quantum dots can reach an average particle size of 5.5 nm. The reaction also has the advantage of being easy to control, and after the reaction is completed, the reaction can be quickly terminated by an ice water bath.
[0012] Preferably, in step (1), the reaction temperature is 80-90°C and the reaction time is 3-5 min.
[0013] The concentration of CsPbBr3 quantum dots should be controlled within a suitable range. When the concentration of quantum dots is too low, the addition of ligand solution may cause quenching and phase change of quantum dots; when the concentration of quantum dots is too high, sufficient ligands may need to be added to cause changes in the photophysical properties of quantum dots.
[0014] Preferably, in step (2), the concentration of CsPbBr3 quantum dots after adding the ligand solution is 2-5 μM.
[0015] In the ligand solution, controlling the molar ratio of didodecyl dimethyl ammonium bromide to lead bromide, as well as the actual dosage of CsPbBr3 quantum dots, didodecyl dimethyl ammonium bromide, and lead bromide, helps to promote the optical properties of quantum dots after ligand exchange to reach the optimal state. It should be noted that the dosage of the above ligands is particularly critical and should be controlled within the preferred range to avoid etching and phase transition of quantum dots caused by excessive ligands.
[0016] After the quantum dots are purified, the synergistic use of didodecyl dimethyl ammonium bromide and lead bromide can repair the lead halide octahedron damaged during the purification process and create a halide-rich environment on the surface of the quantum dots to passivate vacancy defects. In addition, the relatively short-chain didodecyl dimethyl ammonium bromide, which has a stronger interaction with the surface of the quantum dots, partially exchanges with the initial long-chain ligands on the surface of the quantum dots in situ, thereby improving the optical properties and stability of the perovskite quantum dots.
[0017] Preferably, in step (2), the molar ratio of didodecyl dimethyl ammonium bromide to lead bromide in the ligand solution is (2-3):1.
[0018] Preferably, in step (2), the amount of CsPbBr3 quantum dots used is 2-5 nmol; correspondingly, the amount of didodecyl dimethyl ammonium bromide used is 6-12 μmol, and the amount of lead bromide used is 3-6 μmol.
[0019] Preferably, in step (1) and step (2), the purification and dissolution include the following steps: centrifuging in a poor solvent until the precipitation is complete and removing the supernatant; adding a good solvent to the obtained precipitate to completely dissolve it, then performing solid-liquid separation and collecting the supernatant.
[0020] Those skilled in the art can select suitable good solvents and poor solvents according to the physical and chemical properties of the raw materials used in the present invention and the quantum dots produced according to actual conditions. From the perspective of solubility and easy acquisition, poor solvents can be methyl acetate, acetone, ethyl acetate, etc.; good solvents can be n-hexane, toluene, n-octane, etc.
[0021] Further preferably, the poor solvent includes at least one of methyl acetate, acetone, and ethyl acetate; and the good solvent includes at least one of n-hexane, toluene, and n-octane.
[0022] The reactions involved in the above methods are all carried out under an inert atmosphere unless otherwise specified.
[0023] In the operation process of the present invention, strongly confined CsPbBr3 quantum dots are first synthesized under halogen-rich conditions, and then purified by a poor solvent, and then the ligand modification after synthesis is carried out by combining didodecyl dimethyl ammonium bromide and lead bromide, and finally blue light CsPbBr3 perovskite quantum dots with excellent optical properties and stability are obtained. Based on the above technical scheme, the design concept of the present invention is that in order to avoid the problems of chlorine vacancies and halide segregation in chlorine-bromine mixed halogen perovskite, the present invention utilizes the quantum confinement effect to prepare blue light CsPbBr3 perovskite quantum dots, that is, under halide-rich conditions, a cesium precursor is reacted with a lead precursor to obtain a small-sized strongly confined CsPbBr3 quantum dot. Due to the characteristics of the ionic crystals of perovskite itself, the art usually causes the loss of halogen on the surface of the quantum dots and the shedding of ligands after purification using a poor solvent, resulting in the degradation of the performance and stability of the quantum dots. In order to solve this technical problem, the present invention simultaneously adds didodecyl dimethyl ammonium bromide and lead bromide to the purified quantum dots, creates a halide-rich environment on the surface of the quantum dots, and passivates the surface vacancy defects to the maximum extent. In addition, the relatively short-chain, proton-free didodecyl dimethyl ammonium bromide can bond to the remaining uncoordinated lead sites and partially replace the initial long-chain organic ligands on the surface of the quantum dots. The PLQY of the blue light CsPbBr3 perovskite quantum dots obtained by the present invention is close to 100%, and has excellent stability under continuous ultraviolet radiation and environmental conditions.
[0024] It should be noted that the inventor has noticed that in the research stage of this scheme, the prior art (CN114540010A, "A method for preparing blue light perovskite quantum dots") uses lead bromide, didodecyl dimethyl ammonium chloride, etc. as raw materials in the preparation of blue light perovskite quantum dots, and directly introduces organic molecules as replacement ligands into the quantum dot synthesis stage, thereby changing the kinetic process of crystal growth. The raw material type and operation stage of the present invention are selected based on the reasons described below, which are significantly different from the prior art. The inventor has found that due to the low defect tolerance of chlorine-containing perovskite quantum dots, even a small amount of chlorine vacancies will lead to poor efficiency. In addition, mixed halogen perovskites have a tendency to phase separate into domains containing different halogen ion components. Therefore, the present invention selects didodecyl dimethyl ammonium bromide and lead bromide, and the defect tolerance of the prepared bromine-containing perovskite quantum dots is much better than that of the chlorine-containing perovskite quantum dots. Therefore, in the post-synthesis ligand modification, the present invention does not use the chloride salt ligand used in the prior art. The inventors found in the experiment that the optical properties of quantum dots cannot be improved when didodecyl dimethyl ammonium bromide or lead bromide powder is used alone for treatment. And the phenomenon of quantum dot quenching is observed when didodecyl dimethyl ammonium bromide is used alone for treatment. Only when the two are used together can the PLQY be increased from less than 40% to about 100%, while having excellent stability. Based on the above phenomenon, the mechanism of the ligand modification process of didodecyl dimethyl ammonium bromide and lead bromide is that the synergistic effect between didodecyl dimethyl ammonium bromide and lead bromide rebuilds the damaged lead halide octahedron and creates a halide-rich environment on the surface of the quantum dots to repair vacancy defects. In addition, the relatively short-chain, proton-free didodecyl dimethyl ammonium bromide ligand adheres to the surface of the quantum dots, bonds to the uncoordinated lead sites, and exchanges in situ with the original long-chain organic ligands on the surface of the quantum dots, optimizing the PLQY and stability.
[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention provides a method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots, so that the blue light cesium lead bromine perovskite quantum dots have excellent environmental stability and resistance to photobleaching while maintaining excellent optical properties, providing a basis for the preparation of blue light perovskite optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The ultraviolet absorption spectrum and fluorescence spectrum of the strongly confined CsPbBr3 quantum dots prepared in Example 1; Figure 2 The ultraviolet absorption spectrum and fluorescence spectrum of the strongly confined CsPbBr3 quantum dots prepared in Example 2; Figure 3This is a transmission electron microscopy image of the strongly confined CsPbBr3 quantum dots prepared in Example 2; scale 50 nm; Figure 4 The histogram of PLQY variation with time of the strongly confined CsPbBr3 quantum dots prepared in Example 2 under continuous irradiation of ultraviolet lamp; Figure 5 A line graph showing the change in the fluorescence emission peak of the strongly confined CsPbBr3 quantum dots prepared in Example 2 under continuous irradiation with ultraviolet light over time; Figure 6 The time-resolved fluorescence spectra of the strongly confined CsPbBr3 quantum dots prepared in Example 2 before and after being placed in an environment for 60 days; Figure 7 The ultraviolet absorption spectrum and fluorescence spectrum of the strongly confined CsPbBr3 quantum dots prepared in Example 3; Figure 8 The ultraviolet absorption spectrum and fluorescence spectrum of the strongly confined CsPbBr3 quantum dots prepared in Example 4; Fig. 9 The ultraviolet absorption spectrum and fluorescence spectrum of the strongly confined CsPbBr3 quantum dots prepared in Comparative Example 1 without post-synthesis ligand modification; Fig.10 This is a transmission electron microscopy image of the strongly confined CsPbBr3 quantum dots prepared in Comparative Example 1 without post-synthesis ligand modification; scale 50 nm; Fig.11 The histogram of PLQY variation over time of the strongly confined CsPbBr3 quantum dots prepared in Comparative Example 1 without post-synthesis ligand modification under continuous irradiation of ultraviolet light; Fig.12 It is a line graph showing the change of the fluorescence emission peak over time of the strongly confined CsPbBr3 quantum dots prepared in Comparative Example 1 without post-synthesis ligand modification under continuous irradiation of ultraviolet light; Fig.13 This is the time-resolved fluorescence spectrum of the strongly confined CsPbBr3 quantum dots prepared in Comparative Example 1 without post-synthesis ligand modification, which were placed in an environment for 60 days. DETAILED DESCRIPTION
[0027] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0028] Example 1 The method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots comprises the following steps: (1) Weigh 0.3 g of cesium carbonate and dissolve it in a three-necked flask containing 3.2 mL of 1-octadecene and 1.2 mL of oleic acid; heat the mixed solution to 120 °C under vacuum, then introduce argon into the flask and raise the temperature to 150 °C to allow cesium carbonate and oleic acid to react completely; then, keep the cesium precursor solution at 100 °C for later use; 0.6 g of lead bromide, 7 mL of oleic acid, 7 mL of oleylamine and 40 mL of 1-octadecene were placed in a three-necked flask; the mixed solution was heated to 120 °C under vacuum, and then argon was introduced into the flask until the lead bromide was completely dissolved; 2.0 g of zinc bromide, 10 mL of oleic acid and 10 mL of oleylamine were placed in another three-necked flask, and the mixed solution was heated to 140 °C under vacuum; argon was introduced again until the zinc bromide was completely dissolved; then, 14 mL of the zinc bromide mixed solution was slowly injected into the lead bromide mixed solution to form a halogen-rich lead precursor solution; at this time, the halogen-rich lead precursor solution was vacuumed again until no bubbles were generated; then, under an argon atmosphere, the lead precursor solution was slowly cooled to 80 °C; at this time, 3.0 mL of the cesium precursor solution was quickly injected into the lead precursor solution to react for 3 min, and the flask was placed in an ice water bath to terminate the reaction to obtain a CsPbBr3 crude solution; The obtained CsPbBr3 crude solution was centrifuged at 7800 rpm for 5 min to remove unreacted salts; the supernatant was placed at room temperature for 24 h and then centrifuged at 7800 rpm for 5 min; the supernatant was then taken, methyl acetate was added at a volume ratio of 1:2, mixed, and centrifuged at 7800 rpm for 5 min; the supernatant was discarded, and the precipitate was dissolved in toluene to obtain a purified CsPbBr3 solution; the purified quantum dot solution with a concentration of 3 μM and a volume of about 1 mL was taken, methyl acetate was added at a volume ratio of 1:2, mixed, centrifuged at 7800 rpm for 5 min, and the supernatant was discarded to obtain CsPbBr3 quantum dots in the form of solid particles; (2) Dissolve 36.7 mg (0.1 mmol) of lead bromide and 94.4 mg (0.2 mmol) of didodecyl dimethyl ammonium bromide in 4 mL of toluene. Stir the mixed solution in an oil bath at 50 °C until the lead bromide is completely dissolved. Then, take 120 μL of the obtained solution and mix it with 880 μL of toluene to obtain a ligand solution. The ligand solution was added to the above CsPbBr3 quantum dots for post-synthesis treatment to improve the photoluminescence efficiency and stability; the ligand exchange was carried out for 1 hour. When the ligand exchange was completed, methyl acetate was added at a volume ratio of 1:2, mixed, and centrifuged at 7800 rpm for 5 minutes; the supernatant was discarded, and the precipitate was dissolved in toluene to obtain surface-modified blue-light cesium lead bromine perovskite quantum dots.
[0029] Based on the above method, in this embodiment, 6 μmol of didodecyldimethylammonium bromide and 3 μmol of lead bromide are actually used to synthesize ligand-modified strongly confined CsPbBr3 quantum dots, that is, surface-modified blue-light cesium lead bromide perovskite quantum dots.
[0030] Example 2 This example is basically the same as Example 1, except that in step (2), 160 μL of the obtained solution is mixed with 840 μL of toluene to obtain a ligand solution. Therefore, in this example, 8 μmol of didodecyl dimethyl ammonium bromide and 4 μmol of lead bromide are actually used for synthesis, and the synthesized ligand-modified strongly confined CsPbBr3 quantum dots are recorded as DDAB+PbBr2-CsPbBr3.
[0031] Example 3 This example is basically the same as Example 1, except that in step (2), 200 μL of the obtained solution is mixed with 800 μL of toluene to obtain a ligand solution. Therefore, in this example, 10 μmol of didodecyl dimethyl ammonium bromide and 5 μmol of lead bromide are actually used for synthesis.
[0032] Example 4 This example is basically the same as Example 1, except that in step (2), 240 μL of the obtained solution is mixed with 760 μL of toluene to obtain a ligand solution. Therefore, in this example, 12 μmol of didodecyl dimethyl ammonium bromide and 6 μmol of lead bromide are actually used for synthesis.
[0033] Comparative Example 1 This comparative example uses strongly confined CsPbBr3 quantum dots that have not been post-synthesized for comparison, and the preparation method is as follows: Weigh 0.3 g of cesium carbonate and dissolve it in a three-necked flask containing 3.2 mL of 1-octadecene and 1.2 mL of oleic acid; heat the mixed solution to 120 °C under vacuum, then introduce argon into the flask and raise the temperature to 150 °C to allow cesium carbonate and oleic acid to react completely; then, keep the cesium precursor solution at 100 °C for standby use; 0.6 g of lead bromide, 7 mL of oleic acid, 7 mL of oleylamine and 40 mL of 1-octadecene were placed in a three-necked flask; the mixed solution was heated to 120 °C under vacuum, and then argon was introduced into the flask until the lead bromide was completely dissolved; 2.0 g of zinc bromide, 10 mL of oleic acid and 10 mL of oleylamine were placed in another three-necked flask, and the mixed solution was heated to 140 °C under vacuum; argon was introduced again until the zinc bromide was completely dissolved; then, 14 mL of the zinc bromide mixed solution was slowly injected into the lead bromide mixed solution to form a halogen-rich lead precursor solution; at this time, the halogen-rich lead precursor solution was vacuumed again until no bubbles were generated; then, under an argon atmosphere, the lead precursor solution was slowly cooled to 80 °C; at this time, 3.0 mL of the cesium precursor solution was quickly injected into the lead precursor solution to react for 3 min, and the flask was placed in an ice water bath to terminate the reaction to obtain a CsPbBr3 crude solution; The obtained CsPbBr3 crude solution was centrifuged at 7800 rpm for 5 min to remove unreacted salts; the supernatant was placed at room temperature for 24 h and then centrifuged at 7800 rpm for 5 min; then the supernatant was taken, methyl acetate was added at a volume ratio of 1:2, mixed, and centrifuged at 7800 rpm for 5 min; the supernatant was discarded, and the precipitate was dissolved in toluene to obtain a CsPbBr3 solution purified once; a quantum dot solution purified once with a concentration of 3 μM and a volume of about 1 mL was taken, methyl acetate was added at a volume ratio of 1:2, mixed, centrifuged at 7800 rpm for 5 min, and the supernatant was discarded to obtain CsPbBr3 quantum dots in the form of solid particles, which were then dissolved in toluene to obtain strongly confined CsPbBr3 quantum dots without post-synthesis treatment, recorded as CsPbBr3.
[0034] This comparative example is basically the same as step (1) of Example 1, but does not use a ligand solution and corresponding steps for treatment, and is used to study the differences and effects between it and the example.
[0035] Test Example 1 The UV absorption and fluorescence spectra of the quantum dots were recorded using a Cary 100 spectrophotometer and a Cary Eclipse fluorescence spectrophotometer (Agilent Technologies). The PLQY and fluorescence lifetime of the quantum dots were measured using an FLS 1000 steady-state / transient spectrometer with an integrating sphere (Edinburgh Instruments, UK). The UV absorption and fluorescence spectra of the quantum dots prepared in Examples 1-4 and Comparative Example 1, the transmission electron microscopy images of the quantum dots prepared in Example 2 and Comparative Example, and the spectra of the UV light stability and environmental stability analysis are shown in FIG. Figure 1-13 shown.
[0036] TEM images of Example 2 and Comparative Example 1 ( Figure 3 , Fig.10 ) showed that the quantum dots before and after modification with didodecyldimethylammonium bromide and lead bromide ligands were cubic in shape and had a uniform size distribution.
[0037] Depend on Figure 1 , 2 The photophysical properties of the quantum dots prepared in Examples 1-4 and Comparative Example 1 in toluene solution (0.5 μM) obtained from the test results of 7-9 are summarized in Table 1. Figure 6 , 13 The photophysical properties of the quantum dots obtained from the test results before and after being placed under ambient conditions for 2 months are summarized in Table 2.
[0038] Table 1: Quantum dot optical properties
[0039] The histogram of the PLQY of the quantum dots prepared in Example 2 under continuous ultraviolet light irradiation over time shows that within 14 days of illumination, its PLQY is maintained at more than 90%, and its fluorescence emission peak does not shift significantly. The PLQY of the quantum dots prepared in Comparative Example 1 fluctuates within a certain range within 7 days of continuous ultraviolet light irradiation. The slight increase in its PLQY may be attributed to photoactivation, but its fluorescence emission peak undergoes a large red shift on the fourth day of illumination, and continues to shift as the illumination time increases. This is in sharp contrast to Example 2, indicating that the ligand modification strategy after the synthesis of didodecyl dimethyl ammonium bromide and lead bromide can significantly improve the ultraviolet light stability of quantum dots.
[0040] Table 2: Photophysical properties of quantum dots before and after 2 months of exposure to ambient conditions
[0041] The photophysical properties of the quantum dots prepared in Example 2 and the comparative example before and after being placed in ambient conditions for 2 months are summarized in Table 2. After being stored in air for 2 months, the PLQY of the comparative example decreased from 35% to 20%, and the average photoluminescence lifetime (τ ave ) increases, which may be attributed to the emergence of new non-radiative recombination channels. The radiative recombination rate ( k r ) from 1.0×10 8 s -1 Down to 0.5×10 8 s -1 , indicating that the surface defect density of the comparative example increased after being placed under ambient conditions for 2 months. On the other hand, the optical characteristics of the quantum dots prepared in Example 2 remained unchanged, and the PLQY remained above 95%, while maintaining 1.5×10 8 s -1The radiative recombination rate and the non-radiative recombination rate ( k nr ) is close to 0. This indicates that the ligand modification strategy after the synthesis of didodecyldimethylammonium bromide and lead bromide can significantly improve the environmental stability of quantum dots.
[0042] In summary, the present invention obtains perfect crystals with a PLQY close to 100% and a single exponential decay of the photoluminescence lifetime by performing post-synthesis ligand modification on small-sized strongly confined CsPbBr3 quantum dots, i.e., treating them with didodecyl dimethyl ammonium bromide and lead bromide in combination. The synergistic effect of didodecyl dimethyl ammonium bromide and lead bromide repairs the lead halide octahedron damaged during the purification process, and the halogen-rich environment created passivates the surface vacancy defects to the maximum extent. In addition, by ligand exchange, the long-chain organic ligands are replaced with relatively short-chain, more stable quaternary ammonium ligands, thereby improving the stability of the quantum dots. The perovskite quantum dots prepared by the method of the present invention have excellent environmental stability and resistance to photobleaching while maintaining excellent optical properties, providing a basis for the preparation of blue light perovskite optoelectronic devices, and have good application prospects.
[0043] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots, characterized in that: The steps include: (1) adding oleic acid and cesium carbonate to a halogen-rich lead precursor solution to react and obtain a crude CsPbBr3 solution; Purifying, dissolving and recovering the reaction product in the CsPbBr3 crude solution to obtain CsPbBr3 quantum dots; wherein the halogen-rich lead precursor solution is prepared by dissolving lead bromide, zinc bromide and a ligand reagent in an organic solvent; (2) Adding a ligand solution to the CsPbBr3 quantum dots for post-synthesis treatment to improve the photoluminescence efficiency and stability; wherein the ligand solution is prepared by dissolving didodecyl dimethyl ammonium bromide and lead bromide in an organic solvent; after the ligand exchange of the post-synthesis treatment is completed, purifying, dissolving, and recovering the product to obtain surface-modified blue-light cesium lead bromide perovskite quantum dots.
2. The method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots according to claim 1, characterized in that: In the step (1), the molar ratio of lead bromide to zinc bromide in the halogen-rich lead precursor solution is 1:(4-5).
3. The method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots according to claim 2, characterized in that: The ligand reagent is a mixture of oleic acid and oleylamine in a volume ratio of 1:1; the molar ratio of lead bromide to oleic acid in the ligand reagent is 1:(23-28).
4. The method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots according to claim 1, characterized in that: In the step (1), the molar ratio of cesium carbonate to oleic acid is 1:(8-11).
5. The method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots according to claim 1, characterized in that: In the step (1), the reaction temperature is 80-90°C and the reaction time is 3-5 min.
6. The method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots according to claim 1, characterized in that: In the step (2), the concentration of CsPbBr3 quantum dots after adding the ligand solution is 2-5 μM.
7. The method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots according to claim 1, characterized in that: In the step (2), the molar ratio of didodecyl dimethyl ammonium bromide to lead bromide in the ligand solution is (2-3):
1.
8. The method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots according to claim 1, characterized in that: In the step (2), the amount of CsPbBr3 quantum dots used is 2-5 nmol; correspondingly, the amount of didodecyl dimethyl ammonium bromide used is 6-12 μmol, and the amount of lead bromide used is 3-6 μmol.
9. The method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots according to claim 1, characterized in that: In the step (1) and the step (2), the purification and dissolution include the following steps: centrifuging in a poor solvent until the precipitation is complete and removing the supernatant; adding a good solvent to the obtained precipitation to completely dissolve it, and then performing solid-liquid separation and collecting the supernatant.
10. The method for improving the photoluminescence efficiency and stability of blue light cesium lead bromine perovskite quantum dots according to claim 9, characterized in that: The poor solvent includes at least one of methyl acetate, acetone, and ethyl acetate; the good solvent includes at least one of n-hexane, toluene, and n-octane.